Spatial dependency of air pollution in Jabodetabek urban agglomerates cities - Alviana Inas Azizah; Pini Wijayanti; Yusman Syaukat (Center for Science and Technology, IAIN Surakarta, 2024)
Poor air quality is a major issue in the core city of the Jabodetabek urban agglomeration, Jakarta. Unfortunately, this problem is not limited to Jakarta. Other cities in Jabodetabek also face similar challenges, where they have experienced similar fluctuations in their annual average PM2.5 concentrations based on historical data. This indicates that the air quality problem is dependend on the region. The integration of systems and activities among these cities may explain this problem. This spatial dependency is dangerous and can lead to transboundary health effects. Therefore, this research aims to find evidence of this spatial dependency in Jabodetabek. The results show that PM2.5 concentration in Jabodetabek is spatially dependent and exhibits a clustered pattern. The highly concentrated core of the cluster is Depok, the connecting city between the buffer cities and the core city of Jabodetabek. Cities with high-point and mobile hotspot sources, such as South Jakarta, East Jakarta, Bogor, and Bogor City, surround Depok, leading to this concentration.